THE IMPACT OF GAMIFICATION ON STUDENT ENGAGEMENT AND ARABIC LANGUAGE PROFICIENCY: A CASE STUDY IN ARABIC AS A FOREIGN LANGUAGE (AFL) - Husnatul Hamidiyyah Siregar; Humairatuz Zahrah; Rina Haji Omar (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
The teaching of Arabic as a Foreign Language (AFL) presents significant challenges, particularly in terms of student engagement and proficiency. Traditional instructional methods often struggle to maintain student interest, leading to suboptimal learning outcomes. Gamification, the integration of game elements into educational settings, has emerged as a potential solution to enhance both engagement and learning outcomes. This study aims to explore the impact of gamification on student engagement and Arabic language proficiency. A mixed-methods approach was employed, with 60 undergraduate students randomly assigned to either a gamified or a traditional learning group. The experimental group engaged in a gamified learning environment, incorporating points, leaderboards, and interactive tasks. Data were collected through pre- and post-tests measuring language proficiency, a student engagement questionnaire, and qualitative interviews. The results indicated that the experimental group demonstrated significantly higher improvements in language proficiency, particularly in speaking and writing, compared to the control group. Engagement levels were also notably higher in the gamified group, as evidenced by their increased participation and motivation. The findings suggest that gamification is an effective tool for enhancing student engagement and proficiency in AFL, offering an innovative approach to language learning. Further research is needed to explore the long-term effects of gamification and its applicability across different educational contexts.